Prucalopride: the evidence for its use in the treatment of chronic constipation - Coremans, Georges (Dove Medical Press, 2008)
INTRODUCTION: Chronic constipation is a common condition that is difficult to treat. Existing options for the treatment of patients with different subgroups of constipation are limited. A new efficacious and safe drug is needed to limit the frequently observed adverse effects induced by laxatives, to improve general wellbeing and quality of life, and to provide an alternative for enemas or even resectional surgery in patients in whom stimulant laxatives cause disabling adverse effects or fail to increase bowel movement frequency. AIMS: The purpose of this article is to assess the current evidence supporting the use of the selective and high affinity serotonin-4 (5-HT(4)) receptor agonist prucalopride in the management of chronic constipation. EVIDENCE REVIEW: There are now convincing data from phase II and multicenter phase III randomized, double-blind, placebo-controlled trials that prucalopride treatment results in a clinically meaningful increase in the number of spontaneous complete bowel movements, a reduction of perceived severity of symptoms and improved disease-related quality of life in a significant proportion of patients. There is a rapid onset of the effect and the improvement is maintained for at least 12 weeks. Prucalopride in a dose of up to 4 mg per day appeared generally well tolerated and devoid of serious cardiac events. Adverse events, most frequently headache and nausea, are usually mild or moderate and occur mainly during the first days of treatment. Prucalopride should be used with prudence and with careful assessment of the benefit-risk ratio until more clinical and electrophysiologic data become available, because relatively few patients have been exposed to the drug for long periods of time. PLACE IN THERAPY: Prucalopride 1–2 mg once daily may be given to patients suffering from chronic constipation for whom laxatives do not provide adequate relief of their symptoms. Patients with severe constipation and slow transit, who frequently develop tolerance to stimulant laxatives, are also eligible for prucalopride treatment.